Nickel-catalyzed three-component carboamination/cyclization of alkynes to access 2,3-disubstituted quinolines - Gao, Yang; Xing, Jiale; Huo, Yanping; Chen, Qian; Li, Xianwei; Hashmi, A. Stephen K.; Zeng, Zhongyi (Organic letters, 2025)
Presented herein is a nickel-catalyzed chemo- and regioselective three-component tandem carboamination and cyclization of terminal alkynes with organoboronic acids and anthranils for facile and modular access to 2,3-substituted quinolines. In this process, anthranil has dual roles: serving as an electrophilic aminating reagent and a redox buffer to suppress the generation of an off-cycle Ni(0) complex. Moreover, the anionic acetylacetonate (acac) ligand was found to be vital to ensure a productive Ni(I)-Ni(III)-Ni(I) catalytic cycle.
Gesehen am 28.08.2025